A Study on caring character and clinical practice performance of nursing students - Chun, Yeol-Eo; Chun, Yeol-Eo; Shun, Mi-Ja (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study was attempted to investigate the relationship between caring character and clinical practice performance and use it as the basic data for operating the caringcharacter curriculum.    Findings: The average score of the Nursing students' clinical practice performance was 3.68±.56 And the average score of the caring character of nursing students was 212.71±27.53. The relationship between general characteristics of nursing students, performance of clinical practice and caring character was that the higher level of grade and S c h o l a s t i c p e r f o r m a n c e , the higher level of score of the Clinical practice performance and the Caring character. The effect on clinical practice performance, the relationship between caring character and clinical practice performance showed that the higher level of score students’ caring character, the higher level of score students the clinical practice performance (r=.552, p=.000). The results of multiple regression showed that caring character (β = .010, p = .000) and Scholastic performance (β =-.065, p=.042) had significant positive effects on clinical practice performance.